1980
DOI: 10.1139/v80-279
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the magnetite–maghemite–hematite transformation, with special reference to hydrothermal systems

Abstract: . Maghemite, prepared in the usual way (but with exclusion of silica, e.g., from glassware) by precipitation of non-stoichiometric magnetite Fe3-,O,-, in aqueous MOH (M = Na, K) followed by air oxidation, picks up moisture from the air to reach the limiting composition MsH,-sFe50,. where 6 -0.02-0.03 for fresh material, but changes under hydrothermal conditions because of ion exchange. Despite the role of absorbed moisture in stabilizing maghernite, formation of the latter from Fe3-,O,-, is markedly retarded, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 22 publications
2
41
0
Order By: Relevance
“…This is consistent with the relatively sluggish kinetics of Fe 3 O 4 oxidation to Fe 2 O 3 at low-temperature hydrothermal conditions (Swaddle and Oltmann, 1980;Otake et al, 2010), and likely corresponds to surface oxidation effects similar to those identified on magnetite grains after reaction with H 2 O 2 -enriched aqueous solutions at ambient conditions (Costa et al, 2006). Formation of maghemite (cFe 2 O 3 ) was also not observed, however, cannot be excluded, as it appears to be a metastable intermediate phase during low temperature magnetite alteration to hematite (Colombo et al, 1968;Feitknecht and Gallagher, 1970;Swaddle and Oltmann, 1980;Otake et al, 2010). However, Mö ßbauer analysis suggest that magnetite coexisting with H 2 O 2 -HCOOH-bearing fluids develops active Fe 2+ sites during reaction progress as indicated by the decrease in the Fe 3+ /RFe ratio ($0.71) relative to the starting Fe 3+ / RFe composition ($0.84) ( Table 2 and Fig.…”
Section: Resultssupporting
confidence: 79%
“…This is consistent with the relatively sluggish kinetics of Fe 3 O 4 oxidation to Fe 2 O 3 at low-temperature hydrothermal conditions (Swaddle and Oltmann, 1980;Otake et al, 2010), and likely corresponds to surface oxidation effects similar to those identified on magnetite grains after reaction with H 2 O 2 -enriched aqueous solutions at ambient conditions (Costa et al, 2006). Formation of maghemite (cFe 2 O 3 ) was also not observed, however, cannot be excluded, as it appears to be a metastable intermediate phase during low temperature magnetite alteration to hematite (Colombo et al, 1968;Feitknecht and Gallagher, 1970;Swaddle and Oltmann, 1980;Otake et al, 2010). However, Mö ßbauer analysis suggest that magnetite coexisting with H 2 O 2 -HCOOH-bearing fluids develops active Fe 2+ sites during reaction progress as indicated by the decrease in the Fe 3+ /RFe ratio ($0.71) relative to the starting Fe 3+ / RFe composition ($0.84) ( Table 2 and Fig.…”
Section: Resultssupporting
confidence: 79%
“…Maghemite, which has a spinel structure and is often formed as a result of oxidation of magnetite (Swaddle and Oltmann, 1980), is thermodynamically unstable with respect to hematite. However, because transformation of maghemite to hematite is very slow at room temperature, maghemite is a common mineral in nature, including weathered volcanic rocks and some soils (Singer and Fine, 1989;Da Costa et al, 1999;).…”
Section: Metastability Of Maghemitementioning
confidence: 99%
“…Indeed, in nuclear power plants with pressurized water reactors (PWRs), the corrosion of carbon steel generates primarily magnetite in the secondary water vapour circuit due to the reducing conditions in this region. 26 Given that the steam generators (SGs) in such plants transform water into vapour, the corrosion products become concentrated in the circuit, which may eventually lead to fouling and clogging. [27][28][29][30] For this reason, deposited corrosion products must be periodically removed to ensure the integrity and heat exchange capacity of the SGs.…”
Section: Introductionmentioning
confidence: 99%